1986
DOI: 10.1073/pnas.83.15.5544
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a female-specific cDNA derived from a developmentally regulated mRNA in the human blood fluke Schistosoma mansoni.

Abstract: We have isolated and characterized a cDNA clone that is derived from a developmentally regulated mRNA found only in mature female schistosomes. The mRNA is approximately 950 nucleotides in length and is not detectable in immature female schistosomes isolated from single-sex infections, in male worms, or in eggs. During normal bisexual infections, the mRNA species is first detected 28 days after infection (the time of worm pairing) and increases to a high level 35 days after infection, coinciding with the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…There was a strong correlation between the amino acid composition of this protein and the actual composition of the schistosome eggshell (4). This fact, in addition to the biological context in which the mRNA was found, the significant homology in sequence to the silkmoth chorion gene family (3), and the recognition of an eggshell protein of 14 kDa by an antiserum directed against a peptide from the deduced amino acid sequence of the cDNA clone (unpublished data), led us to conclude that the clone encoded a protein that is a major component of the schistosome eggshell (chorion).…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…There was a strong correlation between the amino acid composition of this protein and the actual composition of the schistosome eggshell (4). This fact, in addition to the biological context in which the mRNA was found, the significant homology in sequence to the silkmoth chorion gene family (3), and the recognition of an eggshell protein of 14 kDa by an antiserum directed against a peptide from the deduced amino acid sequence of the cDNA clone (unpublished data), led us to conclude that the clone encoded a protein that is a major component of the schistosome eggshell (chorion).…”
mentioning
confidence: 86%
“…Our data indicated that there were approximately five copies per haploid genome. We also showed that these genes did not amplify or rearrange during schistosome development (1,3).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This antigen named Sm44 has a specific antigenic expression since only serum related to the chronic phase is able to recognize it although in terms of RNA expression the Sm44 antigen of S. mansoni is also present in other evolutionary phases of parasitism but is excluded by the immune system perhaps by some block due to host molecule incorporation or different distribution during the development of the parasite in vertebrate hosts, similar to other antigens described previously (Aronstein & Strand 1983, Harn et al 1985, Davies et al 1986, Stein & David 1986, Bobek et al 1986, Grossman et al 1990, Menrath et al 1995.…”
Section: Discussionmentioning
confidence: 79%